Introduction to Special Issue on Career Education. (December 2019) - Cinamon, Rachel Gali; Hardin, Erin E.; Flum, Hanoch
The current introduction describes several features and outcomes of the changing world of work that serves as conceptual anchors and rational for the career education programs that are included in the current special issue. The four papers target the goal of increasing social equality and the goal to promote fair and sustainable development through career interventions in schools, and therefore reflect an emphasis on social justice and social equality. These interventions target potentially vulnerable groups of students and offer theory-driven models that, with culturally appropriate adjustments to the specific context, schools can include in their curriculum.